Effect on The Decrease Intensity Gymnastics Rheumatic Pain in Patients Gout Arthritis - Fira Dewi Cahyani; Fajar Surachmi; Sri Eny Setyowati (Poltekkes Kemenkes Semarang, 2019)
Background: One of complaints caused by gout arthritis one of which is joint pain. Deposition of urate crystals in joints and tendons to continue and cause damage that will restrict the movement of the joint. Gouty arthritis is characterized by the accumulation of monosodium urate crystals in or around the joints. Monosodium urate crystals activates osteoblasts to secrete cytokines and lower the anabolic functions that will contribute to the destruction juxta-articular bone. Therefore, it is necessary interventions are triggered reduction in pain intensity exercise rheumatism.Purpose: Knowing the influence of gymnastics rheumatism to changes in the intensity of pain in patients with arthritis in the Gunungpati Health Center Working Area.Methods: This study uses a Pre-Experimental one group pre and post-test without control group design. The research sample of 15 people with gout arthritis in Puskesmas Gunungpati Semarang on 1 to 7 April 2019. The sampling technique with purposive sampling and analysis of data processing with the Wilcoxon test.Results: The results showed a pain scale before treatment equal to 4.67 ± 0724 and the scale of pain after treatment decreased to 0.60 ± 0.507. The results of the analysis using the Wilcoxon test shows the p value 0.000 which proves that there is a significant difference between before and after treatment of arthritis exercises to decrease pain scale in patients with gout arthritis.Conclusion: In this study indicate that there is influence of the reduction scale gymnastics rheumatic pain in gouty arthritis patients in Puskesmas Gunungpati Semarang.